EFEKTIVITAS APLIKASI SISTEM KERJA (SIKER) DINAS TENAGA KERJA KOTA SEMARANG - Skolastika Berliana Anniversarani; Ida Hayu Dwimawanti (Journal of Management and Public Policy, 2026)
The development of information technology has encouraged the government to implement digital-based public services through the concept of e-government. One of these innovations is the Employment Information System Application (SIKER) developed by the Semarang City Manpower Office to facilitate the public in obtaining employment information, such as job searching, the issuance of AK1 cards, and access to job training. However, in its implementation, several challenges remain, including limited application usage, lack of socialization, and technical issues that affect the effectiveness of its utilization. This study aims to analyze the effectiveness of the SIKER application in improving public access to employment opportunities using the D&M IS Success Model approach. The research employs a descriptive qualitative method with a field study approach. Data were collected through observation, interviews, and documentation involving employees of the Semarang City Manpower Office and users of the SIKER application. Data analysis is based on the six dimensions of the DeLone and McLean Information System Success Model, namely system quality, information quality, service quality, use, user satisfaction, and net benefits. The results show that the effectiveness of the SIKER application has not yet been fully optimal. System quality and information quality are considered quite good as they are able to provide relevant employment information. However, limitations remain in service quality and application usage, particularly due to the lack of public socialization and the relatively low frequency of application use. Nevertheless, the SIKER application still provides benefits by facilitating access to job information and improving the efficiency of employment services.